2010
DOI: 10.1007/s00125-010-1921-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and C-peptide studies of patients with diabetes in northern Ethiopia: existence of an unusual subgroup possibly related to malnutrition

Abstract: Aims/hypothesis Surveys in northern Ethiopia have demonstrated that apparent type 1 diabetes occurs more frequently than elsewhere in Africa and, indeed, in other parts of the world. We therefore investigated in detail a cohort of diabetic patients from this region to clarify the nature of this type of diabetes. Methods All patients attending the diabetic clinic at Mekelle Hospital in the Tigray region of northern Ethiopia were investigated over a 6 week period. Clinical, demographic and anthropometric data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
4
25
1
Order By: Relevance
“…In Caucasian population, the prevalence of islet cell-associated antibodies in recently diagnosed subjects with T1DM ranged from 80% to 97% (Diabetes Prevention Trial -Type 1 Diabetes Study Group, 2002;Landin-Olsson et al, 1992;Notkins & Lernmark, 2001). The prevalence in our study was comparable to that of Asians (Lee, Ng, Thai, Lui, & Loke, 2001;Todd, Ng, Lui, & Thai, 2004;Zimmet et al, 1993) where it was reported at 5-40% and Africans (Hawa et al, 2005;Lutale et al, 2007;Oli et al, 1981;Panz et al, 2000) which ranged 7-44%, including what was reported in Ethiopia in the 1980s and in 2011 (Gill et al, 2011;Peters et al, 1986). We think that part of the reason why the antibody positivity in our T1DM patients was relatively lower is the fact that most of our T1DM patients were not newly diagnosed as indicated by the mean duration of diabetes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In Caucasian population, the prevalence of islet cell-associated antibodies in recently diagnosed subjects with T1DM ranged from 80% to 97% (Diabetes Prevention Trial -Type 1 Diabetes Study Group, 2002;Landin-Olsson et al, 1992;Notkins & Lernmark, 2001). The prevalence in our study was comparable to that of Asians (Lee, Ng, Thai, Lui, & Loke, 2001;Todd, Ng, Lui, & Thai, 2004;Zimmet et al, 1993) where it was reported at 5-40% and Africans (Hawa et al, 2005;Lutale et al, 2007;Oli et al, 1981;Panz et al, 2000) which ranged 7-44%, including what was reported in Ethiopia in the 1980s and in 2011 (Gill et al, 2011;Peters et al, 1986). We think that part of the reason why the antibody positivity in our T1DM patients was relatively lower is the fact that most of our T1DM patients were not newly diagnosed as indicated by the mean duration of diabetes.…”
Section: Discussionsupporting
confidence: 87%
“…Most studies dealing with the relationship between types of diabetes and autoimmunity were done in European or American populations (Atkinson & Maclaren, 1994). Despite some emerging literature in Africa dealing with autoimmunity and diabetes, our understanding still remains limited and incomplete (Elkadhi et al, 2002;Gill, Tekle, & Reja, 2011;Hawa et al, 2005; (IAA) have been well studied as alternatives to ICA (Bonifacio & Bingley, 1997;Winter & Schatz, 2011). Furthermore, combi-assays for GADA and IA-2A have been shown to be as reliable but more convenient than single assays (Dittler, Seidel, Schenker, & Ziegler, 1998;Siraj, Rogers, Gupta, & Reddy, 2012;Wiest-Ladenburger et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…This same study also showed that only 38.5% of the 91 Haitian children were positive for ≥1 of 3 pancreatic autoantibody, compared to 89.6% in a predominantly Caucasian cohort of children with type 1 DM . These data are similar to previous reports showing lower than usual rates of negative C‐peptide and pancreatic autoantibody positivity in African populations . There is insufficient data to classify with certainty this type of diabetes seen in the Haitian and African populations.…”
Section: Discussionsupporting
confidence: 71%
“…These variant disease phenotypes are characterized by mixed features of both type 1 and type 2 diabetes, thus complicating disease classification on clinical grounds [3]. This challenge may lead to the irrational use of insulin therapy in economically disadvantaged SSA [4], and to inadequate disease management with the risk of a future upsurge of diabetes complications. In addition to the increasing burden of diabetes [1,5], the need for the implementation of additional measures for disease classification has never been more relevant.…”
mentioning
confidence: 99%